Expression features of SOX9 associate with tumor progression and poor prognosis of hepatocellular carcinoma - Guo, Xiaodong (BioMed Central, 2012)
BACKGROUND: SOX9 as a member of the SOX (SRY [sex determining region Y] box) gene superfamily has been previously demonstrated to be a proto-oncogene in a variety of malignancies. However, the clinical significance of SOX9 expression in hepatocellular carcinoma (HCC) remains unclear. The aim of this study was to investigate the expression of SOX9 in HCC and determine its correlation with tumor progression and prognosis. METHODS: One-hundred and thirty HCC patients who had undergone curative liver resection were selected and immunohistochemistry, Western blotting, and quantitative real time polymerase chain reaction (Q-PCR) were performed to analyze SOX9 expression in the respective tumors. RESULTS: Immunohistochemistry, Western blotting, and Q-PCR consistently confirmed SOX9 overexpression in HCC tissues compared with their adjacent nonneoplastic tissues (P ≪ 0.01). Additionally, immunostaining showed more SOX9 positive cells in the higher tumor stage (T3 ~ 4) and tumor grade (G3) than in the lower tumor stage (T1 ~ 2, P = 0.03) and tumor grade (G1 ~ 2, P = 0.01), respectively. Moreover, HCC patients with high SOX9 expression were significantly associated with lower 5-year overall survival (P ≪ 0.01) and lower 5-year disease-free survival (P ≪ 0.01), respectively. The Cox proportional hazards model further showed that SOX9 over-expression was an independent poor prognostic factor for both 5-year disease-free survival (hazards ratio [HR] = 2.621, 95% confidence interval[CI] = 1.548-5.829, P = 0.01) and 5-year overall survival (HR = 3.825, CI = 1.638-7.612, P = 0.003) in HCC. CONCLUSION: Our data suggest for the first time that the overexpression of SOX9 protein in HCC tissues is of predictive value on tumor progression and poor prognosis. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/9029740396926377.